2020
DOI: 10.3390/molecules25225224
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Hydrolase-Inhibitory Activity of Juice-Based Phenolic Extracts in Correlation to Their Anthocyanin/Copigment Profile

Abstract: Red fruits and their juices are rich sources of polyphenols, especially anthocyanins. Some studies have shown that such polyphenols can inhibit enzymes of the carbohydrate metabolism, such as α-amylase and α-glucosidase, that indirectly regulate blood sugar levels. The presented study examined the in vitro inhibitory activity against α-amylase and α-glucosidase of various phenolic extracts prepared from direct juices, concentrates, and purees of nine different berries which differ in their anthocyanin and copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The α-amylase inhibition assay was based on previously described spectrophotometric methods [ 31 , 32 ]. Samples were measured in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The α-amylase inhibition assay was based on previously described spectrophotometric methods [ 31 , 32 ]. Samples were measured in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The α-glucosidase inhibition assay was conducted according to Berger et al (2020) and You et al (2011) [ 31 , 33 ]. Samples were assayed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the extraction procedure can also target certain components and thus increase their concentrations in the final extract. It has been suggested that substances with a smaller sugar group attached inhibit digestive enzymes more successfully [88]. Lipase is the pancreatic enzyme that catalyzes the hydrolysis of triglycerides.…”
Section: Inhibitory Potential Of Analyzed Peach Samples Towards α-Glucosidase α-Amylase Lipase and Acetylcholinesterasementioning
confidence: 99%
“…Previous studies have shown that bioactivity in many plant species significantly reduces early diabetes‐related enzyme activity. In this study, the IC 50 value for α‐glucosidase inhibition of parsnip was 171.15 μg mL −1 , which was higher than that of Aronia (93 μg mL −1 ) and pomegranate (113 μg mL −1 ), a fruit group known to be important for diabetes prevention (Berger et al ., 2020). And previous studies have reported that high antidiabetic activity in carrots is associated with its phenolic acid and flavonoid content, i.e .…”
Section: Resultsmentioning
confidence: 99%